Genetic Characterization of blaCTX–M–55 -Bearing Plasmids Harbored by Food-Borne Cephalosporin-Resistant Vibrio parahaemolyticus Strains in China - Zheng, Zhiwei; Li, Ruichao; Ye, Lianwei; Wai-chi Chan, Edward; Xia, Xiaodong; Chen, Sheng (Frontiers in Microbiology, 2019)
This study aims to investigate and compare the complete nucleotide sequences of the multidrug resistance plasmids pVb0267 and pVb0499, which were recovered from foodborne Vibrio parahaemolyticus isolates, and analyze the genetic environment of blaCTX-M-55 to provide insight into the dissemination mechanisms of this resistance element. Analysis of the sequences of plasmids pVb0267 (166,467 bp) and pVb0499 (192,739 bp) revealed that the backbones of these two plasmids exhibited a high degree of similarity with pR148, a recognized type 1a IncC plasmid recovered from Aeromonas hydrophila (99% identity). The resistance genes, found in both plasmids, included qacH, aadB, arr2, blaOXA-10, aadA1, sul1, tet(A) and blaCTX-M-55, which were mostly arranged in a specific region designated ARI-A. Plasmid pVb0499 was found to possess a larger size of ARI-A than pVb0267, which lacked a mer determination region, a qnrA segment, an aacC3 gene and several mobility-encoding genes. Comparative analysis of resistance island (RI) of these plasmids and others revealed the potential evolution route of these RI sequences. In conclusion, the blaCTX-M-55 and its encoding plasmids were reported for the first time in Vibrio parahaemolyticus of food origin. It is alarming to find that the IncC plasmid and its resistance islands are disseminating in aquatic environment. The potential role of these mobile genetic elements in mediating horizontal transfer of the β-lactamase genes warrants further investigation.